Physical activity and mental health in children and adolescents: a review of reviews. Issue 11 (1st August 2011) - Biddle, Stuart J H; Asare, Mavis
Abstract : Objective: To synthesise reviews investigating physical activity and depression, anxiety, self-esteem and cognitive functioning in children and adolescents and to assess the association between sedentary behaviour and mental health by performing a brief review. Methods: Searches were performed in 2010. Inclusion criteria specified review articles reporting chronic physical activity and at least one mental health outcome that included depression, anxiety/stress, self-esteem and cognitive functioning in children or adolescents. Results: Four review articles reported evidence concerning depression, four for anxiety, three for self-esteem and seven for cognitive functioning. Nine primary studies assessed associations between sedentary behaviour and mental health. Physical activity has potentially beneficial effects for reduced depression, but the evidence base is limited. Intervention designs are low in quality, and many reviews include cross-sectional studies. Physical activity interventions have been shown to have a small beneficial effect for reduced anxiety, but the evidence base is limited. Physical activity can lead to improvements in self-esteem, at least in the short term. However, there is a paucity of good quality research. Reviews on physical activity and cognitive functioning have provided evidence that routine physical activity can be associated with improved cognitive performance and academic achievement, but these associations are usually small and inconsistent. Primary studies showed consistent negative associations between mental health and sedentary behaviour. Conclusions: Association between physical activity and mental health in young people is evident, but research designs are often weak and effects are small to moderate. Evidence shows small but consistent associations between sedentary screen time and poorer mental health.